2008
DOI: 10.1590/s1677-55382008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic outcomes during the learning curve for robotic-assisted laparoscopic radical prostatectomy

Abstract: Objective: We report our initial experience with 62 patients undergoing robotic-assisted laparoscopic prostatectomy (RALP), focusing on the primary parameter of positive surgical margins. The authors demonstrate that excellent oncologic outcomes can be attained with a less steep learning curve than previously hypothesized. Materials and Methods:The first 62 patients undergoing RALP by a single physician (DPD) at our institution between November 2005 and August 2007 were retrospectively assessed. Surgical patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Felix et al compared the results of one surgeon with the highest number of RP operations with other 10 surgeons and found that rates of PSA recurrence and PSM of the surgeon with the highest number of operations were significantly lower (15). Similar results were obtained in other studies (16)(17)(18)(19). In the present study, when the results of the surgeon with the highest number of operations (188 cases) were compared to the remaining 9 surgeons, the PSM rates were observed to be consistent with the literature.…”
Section: Discussionmentioning
confidence: 53%
“…Felix et al compared the results of one surgeon with the highest number of RP operations with other 10 surgeons and found that rates of PSA recurrence and PSM of the surgeon with the highest number of operations were significantly lower (15). Similar results were obtained in other studies (16)(17)(18)(19). In the present study, when the results of the surgeon with the highest number of operations (188 cases) were compared to the remaining 9 surgeons, the PSM rates were observed to be consistent with the literature.…”
Section: Discussionmentioning
confidence: 53%
“…The second issue not addressed by the da Vinci system is the lack of haptic feedback. Shah et al [4] showed that the lack of haptics does not seem to affect surgical margin rates in robotic-assisted laparoscopic prostatectomy (RALP). This is largely due to its improved three-dimensional visualization system that allows for better representation of the tissue being manipulated.…”
Section: Current Robotic Platforms and Interfacesmentioning
confidence: 99%
“…In a study looking at the pathologic outcomes during the learning curve for robotic-assisted laparoscopic radical prostatectomy, Shah et al reported their initial experience with 62 patients undergoing robotic-assisted laparoscopic prostatectomy (RALP), focusing on the primary parameter of positive surgical margins [19]. Their study seemed to suggest that RALP could have equal if not better pathologic outcomes compared to open radical prostatectomy even during the initial series of cases.…”
Section: Trainee Impact On Patient Outcomesmentioning
confidence: 99%